Pengaruh Kinerja Keuangan, Ukuran Perusahaan, dan Kepemilikan Institusional Terhadap Return Saham Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Jasnika, Fiona; Nusantoro, Jawoto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the Effect of Financial Performance, Company Size and Institutional Ownership on Stock Return in mining companies listed on the Indonesia Stock Exchange. The data in this study uses secondary data using the technique of collecting annual financial report data on mining companies with a population of 89 mining companies listed on the Indonesia Stock Exchange. The sampling technique in this study uses purposive sampling techniques and uses several criteria so that 53 mining companies were obtained in the 2019-2021 period. The data analysis used in this study was panel data regression analysis with the help of the Eviews 10 application. Based on data analysis conducted with regression analysis, panel data shows that variables of financial performance and institutional ownership affect stock returns. Meanwhile, the variable size of the company does not affect the return of mining company shares for the 2019-2021 period.